MEDIA FLASH CARD DIGITAL BERBASIS PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS I SD - Ni Luh Gede Eka Putri Aprilianti; Kadek Suranata; Ni Putu Kusuma Widiastuti (STKIP Subang, 2026)
This study was motivated by the low reading ability of first-grade students at SD Negeri 3 Gobleg, which was caused by the lack of interesting and interactive learning media used in the learning process. This study aimed to develop a digital flash card media based on Problem Based Learning (PBL) that is valid, practical, and effective in improving students’ reading skills. The research employed the Research and Development (R&D) method using the ADDIE development model, which consists of analyze, design, development, implementation, and evaluation stages. The subjects of this study were media experts, material experts, teachers, and first-grade students of SD Negeri 3 Gobleg. Data were collected through questionnaires and reading ability tests. The results showed that the developed digital flash card media met the validity criteria based on assessments by media and material experts. In addition, the media was considered practical based on the responses of teachers and students during the learning process. The effectiveness test results indicated an improvement in students’ reading abilities after using the PBL-based digital flash card media. Therefore, the developed media is feasible to be used as a learning medium to improve elementary school students’ reading skills.